2009
DOI: 10.1063/1.3054441
|View full text |Cite
|
Sign up to set email alerts
|

Bimagnetic nanoparticles with enhanced exchange coupling and energy products

Abstract: Bimagnetic FePt/ Fe 3 O 4 nanoparticles with core/shell or heterodimer structure have been prepared using a sequential synthetic method. The dimension of both FePt and Fe 3 O 4 was tuned by varying the synthesis parameters. The as-synthesized bimagnetic nanoparticles were superparamagnetic at room temperature. After being annealed in a reducing atmosphere, the FePt/ Fe 3 O 4 bimagnetic nanoparticles were converted to a hard magnetic nanocomposite with enhanced energy products due to the exchange coupling betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 17 publications
2
65
1
Order By: Relevance
“…Usually the synthesis of the fcc-FePt seeds is performed through the thermal decomposition of Pt(acetylacetonate) 2 and either Fe(CO) 5 [92][93][94][95][96][97][98][99][135][136][137][138] or Fe(acetylacetonate) 2 precursors [94,95,98]. The shell growth has been mainly carried out through the two-steps seeded-growth approach by the thermal decomposition of iron and other transition metal salts [92][93][94][95][96][97][98][99]. Interestingly, the use of excess of iron precursor, Fe(CO) 5 , during the synthesis of FePt nanoparticles can also promote the growth of an iron oxide shell in the so-called one-pot synthesis [135][136][137][138].…”
Section: Synthesis Of Hard-soft Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Usually the synthesis of the fcc-FePt seeds is performed through the thermal decomposition of Pt(acetylacetonate) 2 and either Fe(CO) 5 [92][93][94][95][96][97][98][99][135][136][137][138] or Fe(acetylacetonate) 2 precursors [94,95,98]. The shell growth has been mainly carried out through the two-steps seeded-growth approach by the thermal decomposition of iron and other transition metal salts [92][93][94][95][96][97][98][99]. Interestingly, the use of excess of iron precursor, Fe(CO) 5 , during the synthesis of FePt nanoparticles can also promote the growth of an iron oxide shell in the so-called one-pot synthesis [135][136][137][138].…”
Section: Synthesis Of Hard-soft Nanoparticlesmentioning
confidence: 99%
“…Remarkably, originally, the purpose of the growth of spinel oxide shells was preventing the FePt nanoparticles coalescence during the annealing. However, magnetic characterization demonstrated the exchange coupling between both types of FePt phases (i.e., fcc pre-and L1 0 post-annealed) and the oxide shell [92][93][94][95].…”
Section: Synthesis Of Hard-soft Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Experimental efforts in the past two decades have demonstrated that energy product enhancement can be achieved in low dimensional hard/ soft magnetic systems including physically deposited thin films, [3][4][5] rapidly quenched ribbons, [6][7][8] mechanically milled powders, [9][10][11][12] and self-assembled and core-shell nanoparticle systems. 13,14 But scaling these processes up to bulk materials has remained to be a challenge. Traditional processing techniques such as casting and sintering are ill-suited for producing nanostructured bulk materials since long anneals at high temperatures inevitably lead to excessive grain growth.…”
mentioning
confidence: 99%
“…It is noteworthy that similar conclusions have been drawn from recent experiments on FePt/FeCo thin films 4,5 as well as FePt/Fe 3 O 4 nanoparticle composites. 6 Kneller and Hawig 7 proposed exchange coupled permanent magnets using a combination of hard and soft magnets to achieve high magnetic anisotropy and high saturation magnetization. The hard magnet induces anisotropy in the soft magnet and this effect was suggested to be pronounced when the soft magnetic region is smaller than twice the domain wall width of the hard magnet which is typically 4-5 nm.…”
Section: Introductionmentioning
confidence: 99%